Analisis kelayakan video pembelajaran Bahasa Indonesia kelas V Sekolah Dasar dalam E-Learning WELING - Wigati Sekar Ayu; Siti Istiyati; Septi Yulisetiani (Didaktika Dwija Indria, 2023)
Abstract. This study aims to describe the feasibility of learning Indonesian language learning videos in WELING E-Learning. This research is qualitative descriptive research with a case study approach. The results of this research data come from the evaluation of learning media validation questionnaires using the LORI evaluation framework which has 8 indicators, namely content quality, learning goal alignment, feedback and adaptation, motivation, presentation design, interaction usability, accessibility, reusability, standards compliance which will be divided into 2 aspects, namely media aspects and material aspects. Assessment of the feasibility of learning media was carried out by 3 learning media experts, 3 learning material experts, and 6 elementary school teachers. Apart from using a questionnaire assessment, the video was also tested on fifth grade students at SD Ta'Mirul Islam Surakarta. There are 7 Indonesian learning videos in WELING E-Learning which have very good results to be used as learning media with several revisions.Keywords : Learning media, learning videos, Feasibility of learning media